Prevalence of self-reported halitosis and associated factors in 15 years old male students in Karbala City-Iraq - Rafal A Alawsiy; Nada J MH. Radhi (College of Dentistry/ University of Baghdad, 2021)
Background׃ Halitosis is a common condition and is most often caused by a buildup of bacteria in the mouth because of gum disease, food, or plaque. It can result in anxiety among those affected, it is also associated with depression and symptoms of obsessive compulsive disorder. The aim of this study isto assess the prevalence of self-reported halitosis and associated factors (dental plaque, gingival condition and dental caries) in 15 years old male students in Karbala city in Iraq. Additionally, we studied adolescents' concern with their own breath and whether anyone had ever told them that they had halitosis. Methods׃ A cross sectional observational survey was conducted to15 years old high school students from public and private schools in the city of Karbala, Iraq. The random sample consisted of 400 adolescents from 44 schools. An interview with a structured questionnaire was administered along with measurement of oral parameters (PI, GI, DMF). Results׃ The prevalence of self-reported halitosis was 48.50% according to question one. Prevalence of halitosis according to total score of questionnaire was 86.5%. 13.5% reported that they didn't have halitosis. It is concluded that there is high prevalence of self-reported halitosis, which is associated with a socioeconomic pattern. Most adolescents report concern with their own breath. Dental plaque and gingival status are associated significantly with self-reported halitosis. The high prevalence of self-reported halitosis according to questionnaire among the students may be due to the consumption of garlic or spicy food, in addition dental plaque, gingivitis and dental caries cause increase in volatile silver compound level which cause increase in halitosis. Conclusion׃ Self-reported halitosis is a prevalent situation in about 50% of adolescents in Karbala city. Patients' self-reported halitosis is found to be associated with dental plaque, gingivitis and dental caries.